Development and validation of the motivation to publish scale-scientific articles (EMP-AC) for Peruvian university students - Mamani-Benito, Oscar; Torres-Miranda, Julio; Apaza-Tarqui, Edison Effer; Tito-Betancur, Madona; Morales-García, Wilter C.; Turpo-Chaparro, Josué Edison (Frontiers in Education, 2023)
Objective To design and validate the motivation to publish scale-scientific articles (EMP-AC) for Peruvian university students. Methods This was an instrumental study in which 653 health, business, humanities and engineering students from private and state universities in the 3 regions of Peru participated. The scale was designed in 5 stages following international standards. The internal structure was assessed through both an Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Results The content analysis by expert judges also supported the representativeness of the items related to the construction. The internal structure of the 13-item scale was confirmed through the Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) which showed a structure of three factors: commitment, behavior, and intentional state as initially proposed. Previous analyses of goodness of fit indices were satisfactory (χ2 (167) = 276.93, p < 0.001; CFI = 0.95; TLI = 0.93; RMSEA = 0.07 [0.06–0.08]; SRMR = 0.06). Conclusion The EMP-AC shows initial evidence of validity and reliability; therefore, it can be applied in the study of the motivation to publish scientific articles by Peruvian university students.